Musing on Transformative Teaching and Learning in Higher Education - Gautam, Suresh (Journal of Education and Research, 2017)
I am sitting in my West faced office on the third floor of the building C in Kathmandu University School of Education, Hattiban, Nepal. I am watching outside of the window which refreshed me when I feel exhausted and tired. Today, my tiredness exceeds because I was assigned to write an editorial for the journal published by the school by my colleague. I am thinking of using transformative teaching-learning activities in the higher education of Nepal because my professional life is/will be the part of it.